2010
DOI: 10.1007/s11738-010-0470-5
|View full text |Cite
|
Sign up to set email alerts
|

HMG-CoA reductase limits artemisinin biosynthesis and accumulation in Artemisia annua L. plants

Abstract: In vivo modulation of HMG-CoA reductase (HMGR) activity and its impact on artemisinin biosynthesis as well as accumulation were studied through exogenous supply of labeled HMG-CoA (substrate), labeled MVA (the product), and mevinolin (the competitive inhibitor) using twigs of Artemisia annua L. plants collected at the preflowering stage. By increasing the concentration (2-16 lM) of HMG-CoA (3-14 C)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Similarly, inhibition in artemisinin accumulation was observed in the presence of fosmidomycin, the competitive inhibitor of 1-deoxy-Dxylulose 5-phosphate reductase (DXR). Artemisin is a sesquiterpene-lactone isolated from the aerial parts of Artemisia annua plants that is biosynthesised by MVA pathway (Ram et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, inhibition in artemisinin accumulation was observed in the presence of fosmidomycin, the competitive inhibitor of 1-deoxy-Dxylulose 5-phosphate reductase (DXR). Artemisin is a sesquiterpene-lactone isolated from the aerial parts of Artemisia annua plants that is biosynthesised by MVA pathway (Ram et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Esculin content in leaf extract was quantified by RP-HPLC method [36]. In conclusion, result presented here clearly illustrate the positive impact of calcium phosphate nanoparticles mediated trasformation on biosynthesis of esculin via natural mean without the application of biological or other previously used systems having low transformation frequency [41]. 8).…”
Section: Evaluation Of Enhanced Biosynthesis Of Esculinmentioning
confidence: 66%
“…pDNA/chitosan nano-complexes as gene delivery system were reported by investigator for gene therapy [41]. Necrosis of leaf segments in explants observed within 24h of incubation in untransformed plants.…”
Section: Transformation Of C Intybus Via Calcium Phosphate Nanopartimentioning
confidence: 98%
“…Transcriptional levels of HMGR and FDS are of particular relevance because previous studies have shown that by increasing expression of these genes, the amount of artemisinin increases several-fold (Chen et al, 2000;Aquil et al, 2009;Jing et al, 2009;Liu et al, 2010;Arsenault et al, 2010;Wang et al, 2011;Lin et al, 2011;Alam et al, 2014). On the other hand, Ram et al (2010) studied the in vivo activity of HMGR and its influence on artemisinin and reported that HMGR activity limits the accumulation of artemisinin biosynthesis in A. annua. Therefore, HMGR was reported as a key regulatory enzyme of the mevalonate pathway.…”
Section: Expression Analysis Of Artemisinin Biosynthetic Genesmentioning
confidence: 99%